Mitigasi Bencana Pada Layanan Jasa Penyedia Akomodasi Pariwisata Pulau Nusa Lembongan Kabupaten Klungkung - Wilasasti, Ayu Asri; Sukana, I Made (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i02.p15, 2019)
This research is conducted in Nusa Lembongan Island, Klungkung Regency. Based on the Indonesian laws no 24 in 2007 about Disaster management, it states that the territory of the united republic of Indonesia has geographical, hydrological, and demographic conditions that are very possible in the occurience of disaster. The aimed of this research is to discover the industry of disaster mitigation on the service provider of tourism accommodation in Nusa Lembongan IslandKlungkung Regency. The data in this research is a qualitative data. the sourch of the primer and sekunder datas. Were collected through observation, interview and documentation. The determination technique of informan use is proposive procedure.                   The result of this research showed that hotel, resort and bungalow accommodation has prepared themselves to facing disaster in the preparation, the service provider prepare themselves by disaster knowledge, mitigation tools and disaster sign, also mitigation practive when disaster happens. Four from five accomoation has prepared more for fire accidents meanwhile the other one is prepped more to face Tsunami.                   As for suggestions that can be given to accomoation service and govermeuntis being able to set an example of what is good and reaffirm the regent is rules applied through the SK about mitigation disaster. The local communities are expected to know more about natural phenomena and to cooperate with the government to gain knowledge.The researcher hopes this resech can be sort knowledge about disaster mitigation on accommodation provider so in the future there will be more deep.   Keywords : Mitigation of disaster, Accomodation, Industry of tourism, Nusa Lembongan Island